Structural and successional variability of periphytic algal community in a Amazonian lake during the dry and rainy season (Rio Branco, Acre) Variação estrutural e sucessional da comunidade de algas perifíticas em lago amazônico durante o período seco e chuvoso - Raquel C.S França; Maria Rosélia Marques Lopes; Carla Ferragut (Acta Amazonica, 2011)
The colonization process and successional patterns of a periphytic algal community were evaluated in a Amazonian Viveiro Lake (Rio Branco, Acre, Brazil). Sampling was performed over a period of 35 days; at four-day intervals for 20 days, and then at five-day intervals. Water sampling for physical, chemical and biological analyses was done during the dry and rainy season. Glass slides were used as artificial substrates for periphyton colonization. The structural community was evaluated through population density, algae class, diversity indices and descriptive species. Species richness, diversity and evenness increased as succession progressed. While density of Bacillariophyceae, Euglenophyceae and Zygnemaphyceae increased with succession, Cyanobacteria remained dominant. Synechocystis aquatilis, Synechocystis diplococcus and Navicula pseudolanceolata were the main descriptive species in both the dry and rainy season. Cymbela tumida, Frustulia rhomboides, Trachelomonas lacustris and Closterium acicularis was correlated with an increase in hydrologic level during the rainy season. Conversely, the density of Chlamydomonas sp., Chroomonas nordstedtii, Trachelomonas volvocinopsis, Trachelomonas volvocina and Synechococcus linearis was correlated with an increase in water transparency during the dry season. In general, the periphytic algal community showed high diversity and species richness independent of season. Season also had little influence on representation of algae class and main descriptive species. However, successional patterns varied by season, and changes in hydrologic levels acted directly on the succession path of periphytic algae. More research on periphyton dynamics is needed to improve our understanding of tropical lake ecosystems, especially in Amazonian. A colonização e o modelo sucessional da comunidade de algas perifíticas foram avaliados no amazônico Lago do Viveiro (Rio Branco, Acre, Brasil). Amostragens foram realizadas no período de 35 dias com intervalos de quatro dias nos primeiros 20 dias e cinco dias no final. Foram realizadas amostragens da água para a determinação das variáveis físicas, químicas e biológicas no período seco e chuvoso. Lâminas de vidro foram usadas para a colonização do perifíton. A estrutura da comunidade foi avaliada através da densidade populacional, classes algais, índices de diversidade e espécies descritoras. A riqueza de espécies, diversidade e equitabilidade aumentaram com o avanço da sucessão. A densidade de Bacillariophyceae, Euglenophyceae e Zygnemaphyceae aumentaram com o avanço da sucessão, mas Cyanobacteria permaneceu dominante. Synechocystis aquatilis, Synechocystis diplococcus e Navicula pseudolanceolata foram descritoras da comunidade no período seco e chuvoso. Cymbela tumida, Frustulia rhomboides, Trachelomonas lacustris e Closterium acicularis foram correlacionadas com o aumento do nível hidrológico no período seco e chuvoso. Contrapondo, a densidade de Chlamydomonas sp., Chroomonas nordstedtii, Trachelomonas volvocinopsis, Trachelomonas volvocina e Synechococcus linearis foram correlacionadas com o aumento da transparência da água durante o período seco. De modo geral, a comunidade de algas perifíticas apresentou elevada diversidade e riqueza de espécies independentemente do período climático. O período climático apresentou pouca influência sobre a representatividade das classes algais e espécies descritoras. Contudo, os modelos sucessionais foram diferentes em cada período climático e as mudanças no nível hidrológico atuaram diretamente sobre a sucessão das algas perifíticas. Mais pesquisas sobre a dinâmica do perifíton são necessárias para melhorar a compreensão dos ecossistemas lacustres tropicais, especialmente na Amazônia.